Selection and Characterization of Bacteriocinogenic Lactic Acid Bacteria from the Intestine of Gilthead Seabream (Sparus aurata) and Whiting Fish (Merlangius merlangus): Promising Strains for Aquaculture Probiotic and Food Bio-Preservation - Sarah Cheriet; Sana Lengliz; Amel Romdhani; Paul Hynds; Mohamed Salah Abbassi; Taoufik Ghrairi (Life, 2023)
This study sought to evaluate the probiotic properties and the food preservation ability of lactic acid bacteria isolates collected from the intestines of wild marine fishes (gilthead seabream (Sparus aurata) (n = 60) and whiting fish (Merlangius merlangus) (n = 40)) from the Mediterranean sea in the area of Mostaganem city, Algeria. Forty-two isolates were identified as: Enterococcus durans (n = 19), Enterococcus faecium (n = 15), Enterococcus faecalis (n = 4), Lactococcus lactis subp. lactis (n = 3), and Lactobacillus plantarum (n = 1). All isolates showed inhibition to at least one indicator strain, especially against Listeria monocytogenes, Staphylococcus aureus, Paenibacillus larvae, Vibrio alginolyticus, Enterococcus faecalis, Bacillus cereus, and Bacillus subtilis. In all collected isolates, PCR analysis of enterocin-encoding genes showed the following genes: entP (n = 21), ent1071A/B (n = 11), entB (n = 8), entL50A/B (n = 7), entAS48 (n = 5), and entX (n = 1). Interestingly, 15 isolates harbored more than one ent gene. Antimicrobial susceptibility, phenotypic virulence, and genes encoding virulence factors were investigated by PCR. Resistance to tetracycline (n = 8: tetL + tetK), erythromycin (n = 7: 5 ermA, 2 msrA, and 1 mef(A/E)), ciprofloxacin (n = 1), gentamicin (n = 1: aac(6′)-aph(2″)), and linezolid (n = 1) were observed. Three isolates were gelatinase producers and eight were α-hemolytic. Three E. durans and one E. faecium harbored the hyl gene. Eight isolates showing safety properties (susceptible to clinically relevant antibiotics, free of genes encoding virulence factors) were tested to select probiotic candidates. They showed high tolerance to low pH and bile salt, hydrophobicity power, and co-culture ability. The eight isolates showed important phenotypic and genotypic traits enabling them to be promising probiotic candidates or food bio-conservers and starter cultures.